Legal Protection of Regional Athletes' Rights in Retirement (Study of East Kalimantan Provincial Athletes) - Fiqri, Muhammad Zilmy; Kurnia, Mahendra Putra; Arifudin, Nur (Journal Research of Social Science, Economics, and Management, 2025)
Using a socio-legal methodology, this study seeks to identify two primary discussion points: The author's first goal is to understand and examine how Indonesia's legal system protects athletes' rights in East Kalimantan upon their retirement. Second, how is the creation of equitable legal protection in the province of East Kalimantan doing in terms of maximizing the rights and assurances offered to athletes upon their retirement. Based on the results of the study, it shows that the legal protection of athletes in East Kalimantan province is caused by negligence by government institutions and private parties in fulfilling the rights of athletes in retirement or retirement. The protection refers to Articles 99 to 100 of Law Number 11 of 2022 concerning Sports, Law No. 24 of 2011 and Regional Regulation Number 5 of 2016 concerning the implementation of Sports. However, in its implementation, there is no explicit regulation that regulates the amount of social security rights that athletes can obtain in retirement. The protection refers to Articles 99 to 100 of Law Number 11 of 2022 concerning Sports, Law No. 24 of 2011 and Regional Regulation Number 5 of 2016 concerning the implementation of Sports. However, in its implementation, there is no explicit regulation that regulates the amount of social security rights that athletes can obtain in retirement. Settlement can be done through mediation and revising the relevant laws.